Penggalihan kebutuhan berdasarkan pengalaman user persona untuk meningkatkan ekspektasi pengguna terhadap LMS - Salma Auliannisa; Wahyu Andhyka Kusuma (Politeknik Siber Cerdika Internasional, 2022)
Lately, many of the educational circles use LMS to conduct electronic learning. This is because the COVID-19 pandemic has an impact on the teaching and learning process. Therefore, the government took a policy to reduce the spread of the COVID-19 virus by carrying out social restrictions. This requires that teaching and learning activities, which were initially carried out in person and face-to-face, must be done online or remotely, which of course creates new problems for teachers and students. Some of the problems that exist include students' ignorance when the lecturer gives assignments, or even the internet problems faced by some students. In previous studies, several researchers used a usability scale to obtain data from multiple users. However, in this case, the authors collected data through interviews with several users regarding what they needed regarding LMS. From the data obtained, the researcher thinks that the LMS is less effective for online learning due to the lack of features contained therein. One of the features needed by some users is the notification feature to find out the latest information that has been shared.